The Effect of Canva-Based Learning Media on Students’ Learning Outcomes in Writing Procedural Texts - Fitriani; Rizki Lestari; Rahmi Syafriyeti (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2025)
This study aims to evaluate the effect of using Canva-based learning media on students’ learning outcomes in writing procedural texts at the eleventh-grade level. The research employed a quantitative approach with a quasi-experimental design using a nonequivalent control group. The participants consisted of two classes, XI A and XI B, totaling 58 students. Sampling was conducted through a purposive technique to ensure comparable characteristics between the two groups. Data were collected through observation, written tests, and documentation to measure students’ mastery of procedural text writing. The findings showed that the average score of the experimental class reached 85.68, while the control class obtained an average of 79.31. The hypothesis test produced a calculated t-value of 4.584, which was higher than the t-table value of 2.003, indicating a significant difference in learning outcomes between the two classes. These results suggest that Canva-based learning media effectively improved students’ ability to organize ideas, use appropriate vocabulary, and structure procedural texts coherently. The novelty of this study lies in the integration of Canva not merely as a visual design tool but as an instructional medium that supports writing skill development through creative, technology-enhanced learning experiences aligned with modern classroom needs.